New fossil taxa of Ischalia Pascoe (Coleoptera: Ischaliidae) from Eocene Baltic amber - Alekseev, Vitalii I.; Bukejs, Andris (Zootaxa, 2017)
Two new fossil species of false fire-colored beetles (Coleoptera: Ischaliidae), Ischalia dohnaturris sp. nov. and I. danieli sp. nov., are described and illustrated from Eocene Baltic amber. The fossil species I. dohnaturris sp. nov. is considered to be the first macropterous representative of the subgenus Eupleurida LeConte. The second species, I. danieli sp. nov., is placed in the newly described subgenus Telnovia subgen. nov. The subgeneric characters of Ischalia are briefly discussed. A key to fossil species of Ischalia is also provided.